Hungry for more: Low resident social engagement is indirectly associated with poor energy intake and mealtime experience in long-term care homes. (1st April 2021) - Morrison-Koechl, Jill; Wu, Sarah A.; Slaughter, Susan E.; Lengyel, Christina O.; Carrier, Natalie; Keller, Heather H.
Abstract: Mealtimes in long-term care (LTC) homes provide social engagement and nutritional intake to residents. Psychosocial challenges may detract from the mealtime experience, resulting in low food intake and increased risk of malnutrition. This study explores the independent effects of psychosocial factors on energy intake among LTC residents. Secondary data (Making the Most of Mealtimes [M3]) from residents in 32 Canadian LTC homes were analyzed. Data included 3-day weighed food intake, mealtime care actions taken by staff, loss of appetite, eating challenges, and other resident characteristics. Psychosocial factors (i.e., social engagement, depression, and aggressive behaviours) were measured using standardized scales. The independent effects of psychosocial factors on energy intake were tested using bivariate and linear regression analyses adjusted for loss of appetite, eating challenges, and demographic characteristics. The final sample included 604 residents (mean age = 86.8 ± 7.8 years; 31.8% male). Of the three psychosocial factors, only social engagement was associated with energy intake. Low social engagement was associated with cognitive and functional challenges, malnutrition risk, more task-focused mealtime actions by staff, and lower energy intake. Simple regression analysis revealed that individuals with low social engagement ate 59.6 kcal less per day (95% CI = −111.2, −8.0). This significant association remained when adjusting for loss of appetite, but was no longer significant when adjusting for eating challenges. Low social engagement occurs concurrently with physical and functional challenges among LTC residents, affecting both the nutritional and social aspects of mealtimes. Emphasis on socializing during mealtimes, especially for those with eating challenges (e.g., requiring assistance), may contribute to improved resident appetite and quality of life.